2013
DOI: 10.1097/nrl.0b013e31827c6bdd
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic Findings in Dementia With Lewy Bodies

Abstract: Introduction The clinical features of dementia with Lewy bodies (DLB) during wakefulness are well known. Other than REM sleep behavior disorder (RBD), only limited data exists on other sleep disturbances and disorders in DLB. We sought to characterize the polysomnographic (PSG) findings in a series of DLB patients with sleep-related complaints. Methods Retrospective study of patients with DLB who underwent clinical PSG at Mayo Clinic Rochester or Mayo Clinic Jacksonville over an almost 11 year span for evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 11 publications
1
50
0
1
Order By: Relevance
“…It is characterized by cognitive decline, Parkinsonism, visual hallucinations, cognitive/behavioral fluctuations, and dream-enactment behaviors [3, 4]. Heitz et al .…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by cognitive decline, Parkinsonism, visual hallucinations, cognitive/behavioral fluctuations, and dream-enactment behaviors [3, 4]. Heitz et al .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rapid Eye Movement sleep behaviour disorder, severe autonomic dysfunctions, such as orthostatic hypotension, repeated syncope and systematised delusions, can be seen in patients with DLB 21. Furthermore, in a previous study, we reported a high frequency of periodic limb movements in patients with DLB 22.…”
Section: Discussionmentioning
confidence: 66%
“…reported PSG findings in 78 patients with DLB. The 65 patients who attained REM sleep had RWA during PSG . One patient without a history of RBD had RWA, which is consistent with subclinical RBD.…”
Section: Discussionmentioning
confidence: 96%